Knight's Microsoft business intelligence 24-hour trainer leveraging Microsoft SQL server integration, analysis, and reporting services with Excel and SharePoint - Knight, Brian 1976- (Wiley Pub., 2010)
Provides information on using the Microsoft business information tools to perform analysis and reporting using Excel and SharePoint.
Print version record
Keywords: Business intelligence -- Computer programs; Management information systems; Management Information Systems; Systèmes d'information de gestion; COMPUTERS; Management Information Systems; Management; Computer software